Polycystic kidney disease increases the stoke incidence in Taiwan: A retrospective population-based cohort study using National Health Insurance DatabaseAt a glance of commentary - Lukas Jyuhn-Hsiarn Lee; Li-Kai Tsai; Yu-Yin Chang; Jung-Der Wang; Juliana Tze-Wah Kao (Biomedical Journal, 2022)
Background: Few studies documented incidence rates of different types of stroke among patients with polycystic kidney disease (PKD). Methods: We conducted a retrospective cohort study based on the National Health Insurance (NHI) Database of Taiwan. The PKD cohort comprised patients aged≥20 years diagnosed with PKD using inpatient claims from 1998 to 2011, excluding prior stroke. The reference cohort was established by inpatients without PKD using 1:4 frequency-matched with age, gender, and baseline comorbidities. The two cohorts were followed-up until stroke hospitalization, death, withdrawal from the NHI program, or the end of 2012. To account for competing risks of death, we used multivariable competing risks regression models to estimate sub-distribution hazard ratio (SHR) adjusted for age, gender, baseline comorbidities and end stage renal disease. Results: 7837 PKD patients and 31,211 reference subjects were followed up through 2012. A total of 955 cases of stroke were identified in the PKD cohort, including 441 ischemic stroke (IS), 289 intracranial hemorrhage (ICH), 73 subarachnoid hemorrhage (SAH) and 232 other stroke. The incidence rates of overall stroke, IS, ICH, and SAH were 21.3, 10.2, 6.8, and 1.7 per 1000 person-years, respectively. The SHR for overall stroke was 1.39 [95% confidence interval (CI) 1.28–1.50]. SAH had the highest SHR, 4.55 [95% CI 3.26–6.37], followed by ICH (1.84), other stroke (1.24), and IS (1.22). Conclusion: This study illustrated the incidence rates of stroke among inpatient of PKD. The PKD patients had a significantly increased risk of all kinds of stroke after adjusting baseline comorbidities.